2018
DOI: 10.1029/2018gb005880
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Atmospheric Acid Processing on the Global Deposition of Bioavailable Phosphorus From Dust

Abstract: The role of dust as a source of bioavailable phosphorus (Bio‐P) is quantified using a new parameterization for apatite dissolution in combination with global soil data maps and a global aerosol transport model. Mineral dust provides 31.2 Gg‐P/year of Bio‐P to the oceans, with 14.3 Gg‐P/year from labile P present in the dust, and an additional 16.9 Gg‐P/year from acid dissolution of apatite in the atmosphere, representing an increase of 120%. The North Atlantic, northwest Pacific, and Mediterranean Sea are iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 89 publications
(179 reference statements)
4
19
0
Order By: Relevance
“…He et al (2011) studied the atmospheric dry and wet deposition of P in Singapore and reported that DIP comprised 38 % of TP in aerosols. In the dust samples of this study, however, the P solubility was approximately 8 %, which was close to the value of 10 % measured in dust aerosols collected at the Mediterranean coast (Carbo et al, 2005;Herut et al, 2002;Nenes et al, 2011) but was considerably lower than the value of 20 % measured in Asian dust at the coastal site of the East China Sea and in African dust in the western subtropical North Atlantic (Guo et al, 2014;Zamora et al, 2013). There are few available data for P solubility in the marine atmosphere (Hsu et al, 2014;Baker et al, 2006a, b), and the limited data show that the solubility of P in marine aerosols is generally higher than that in coastal aerosols ( Table 1).…”
Section: P Solubilitysupporting
confidence: 87%
See 3 more Smart Citations
“…He et al (2011) studied the atmospheric dry and wet deposition of P in Singapore and reported that DIP comprised 38 % of TP in aerosols. In the dust samples of this study, however, the P solubility was approximately 8 %, which was close to the value of 10 % measured in dust aerosols collected at the Mediterranean coast (Carbo et al, 2005;Herut et al, 2002;Nenes et al, 2011) but was considerably lower than the value of 20 % measured in Asian dust at the coastal site of the East China Sea and in African dust in the western subtropical North Atlantic (Guo et al, 2014;Zamora et al, 2013). There are few available data for P solubility in the marine atmosphere (Hsu et al, 2014;Baker et al, 2006a, b), and the limited data show that the solubility of P in marine aerosols is generally higher than that in coastal aerosols ( Table 1).…”
Section: P Solubilitysupporting
confidence: 87%
“…Aerosol P from anthropogenic sources usually has a higher solubility than that from mineral sources. The reason is that anthropogenic P tends to associate loosely with particulates, dissolve more readily than mineral P and, consequently, interact easily with acid gases to produce more bioavailable P (Herut et al, 2002;Baker et al, 2006a, b;Anderson et al, 2010;Hsu et al, 2014;Herbert et al, 2018). Our results indicate that the P solubility was approximately 35 % in the aerosols when the fraction of anthropogenic P in the TP was more than 70 %.…”
Section: Aerosol Sources and Mineral Dust Loadingmentioning
confidence: 62%
See 2 more Smart Citations
“…The atmospheric depositional flux of DIN is from Vet et al (). The atmospheric depositional flux of P to the North Pacific is the total phosphorus flux (Herbert et al, ). The fluxes from the subsurface layer by water mixing in the North Pacific Ocean gyre are from Letscher et al ().…”
Section: Resultsmentioning
confidence: 99%